2011
DOI: 10.1016/j.nancom.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-based physical channel identification in molecular nanonetworks

Abstract: Nanotechnology is the engineering of functional systems at the molecular/atomic level. Nanomachines are expected to be very simple devices, but nanonetworks, the association of nanomachines, are expected to increase their capabilities, allowing them to share information in order to perform more complex tasks and increase their range of operation. How nanomachines will communicate is currently under In this work, the diffusion-based MC channel is explored in order to extract its main communication metrics, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…Using the equation μ=dv mentioned in Section 2, we choose the average propagation delay of the information molecules from 1 to 5 μs which is within the feasible range. The diffusion coefficient D is set to 1–10 μm 2 /μs, which is used in [36,40]. According to the equation λ=d22D mentioned in Section 2, we choose the shape parameter λ=1, which is within the feasible range.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Using the equation μ=dv mentioned in Section 2, we choose the average propagation delay of the information molecules from 1 to 5 μs which is within the feasible range. The diffusion coefficient D is set to 1–10 μm 2 /μs, which is used in [36,40]. According to the equation λ=d22D mentioned in Section 2, we choose the shape parameter λ=1, which is within the feasible range.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Particle positions are assumed to lie on lattice points; in addition, nano machine positions are assumed to be fixed. The Java-based simulator illustrated in [20]- [22], called N3Sim, emulates a two-dimensional particle Brownian diffusion model, with 3D extensions in specific conditions. Propagation phenomena includes inertia forces and particle collisions.…”
Section: A Related Work In Biological Nanoscale Communicationsmentioning
confidence: 99%
“…Garralda et al have used N3Sim simulator in [16] which simulates propagation of individual molecule using BM and verifies the results using Fick's Laws. Yet another attempt to combine deterministic and stochastic approaches can be found in [17] where propagation is modelled as diffusion followed by particle location displacement which is stochastic by nature.…”
Section: Propagation Dynamicsmentioning
confidence: 99%
“…Therefore, the higher the diffusion coefficient the narrower the received pulses will be and in turn, may provide higher data rate in case of timing channels [23]. Fig.4 Transmission and reception of two pulses and their addition to prove linearity of molecular channel [16] Fig.5 Transmission and reception of a single pulse and its time shifted version to prove temporal invariance of molecular channel [16] Garralda et al have shown in [16] that a diffusion based MC channel in a linear time invariant channel, in single as well as multi transmitter scenarios. It is very clear from figure 4 that the superposition principle holds true in the example of 2 different pulses as well as their addition in a diffusive channel.…”
Section: Simulationsmentioning
confidence: 99%